Challenging a range of high pressure processing parameters to inactivate pathogens in orange juice. Issue 4 (1st October 2020) - Petrus, Rodrigo Rodrigues; Churey, John Joseph; Worobo, Randy William
ABSTRACT: Among the non-thermal food technologies, high pressure processing (HPP) is currently the most widespread intervention in the juice industry. The study herein was conducted to challenge a wide range of pressure (401–599 MPa) and dwell time (87–313 s) in orange juice processing. The parameters were combined and targeted a minimum of 5-log cycle reductions in a cocktail for the pathogens of reference – Escherichia coli O157:H7, Salmonella enterica e Listeria monocytogenes – inoculated into the juice. Eleven trials were carried out based on a central composite rotational design. All combinations of pressure and dwell time succeeded in reducing all pathogens. E. coli O157:H7 exhibited more resistance to HPP than S. enterica and L. monocytogenes . The findings demonstrated that relatively low pressure (∼400 MPa) and short dwell time (∼200 s) can be successfully used to produce a safe orange juice.